Aluno, um leitor em potencial - Honda, Sandra Delmonte Gallego (2016)
Although not all young people have the reading habit, we believe that all are potential readers; this is not always exploited by the teacher who, in turn, does not observe the student's ability and/or willingness to strengthen the reading, especially literary reading.Thus, the purpose of this research is to analyze the perspective of high school students related to encouragement of reading in Portuguese classes, specifically in Literature. The students are the research subject, as their answers will be the basis for the data collection and analysis. The survey was conducted in an east zone State School in São Paulo, downtown, focusing on students of the 2nd year of high school only. The qualitative method was the one that best responded to the proposed purposes for this research, i.e., the understanding of a real approach which could have the opinions of respondents themselves as a result. We used the observation and a questionnaire with open and closed questions as our method, so we could identify subjects with potential or a reader profile, according to their own personal considerations. In the methodological part, this research reviews the studies of LÜDKE, Menga; ANDRÉ, Marli E.D.A. (1986). FREIRE, Paulo (2009, 2010, 2011); PETIT, Michèle (2008, 2009, 2013) and BAPTISTA, Ana M.H (2011) served as a support for the theoretical foundation, as well as for data analysis obtained. The conclusions of this study enable a much closer understanding of expectations of the potential reader student.